Pemahaman Orang Tua Di Paud Az-Zahra Dalam Menstimulasi Perkembangan Anak Melalui Pendekatan Steam - Nurakhmaliyah, Siti; Usman, Nurodin (Prosiding University Research Colloquium, 2021)
his research is motivated by the lack of the ability of parents to stimulate children’s development at home. Covid 19, which has hit almost all countries, demands changes in various aspects of life, including education. The Covid 19 pandemic also requires parents to act as teachers at home. However, in practice, not all parents are optimal in carrying out their roles, therefore researchers are interested in conducting research on parental understanding in stimulating children’s development through the STEAM approach. The research subjects were parents at the Az-zahra Early Childhood Education Institute Yogyakarta. The purpose of this study was to determine the extent to which parental understanding in stimulating children’s development while learning from home in terms of the STEAM approach. The subjects of this study were 20 parents of children aged 4-7 years. Characteristics of research subjects were parents who had attended training on virutial STEAM-filled learning. This study uses qualitative research methods, which focus on understanding, implementing and evaluating parental activities in stimulating early childhood development. Data obtained from questionnaires, virtual interviews, and documents. The results of this study obtained data that in the principle component of STEAM implementation which consists of 6 variables an average percentage of 75% is obtained, while in the STEAM implementation formula component, the percentage is 83.5%, indicating that parents can understand the STEAM approach and apply it in stimulating children’s development while learning from home through materials and tools around the home environment.